Inverted CsPbI3 perovskite solar cells with all solution processed layers fabricated in high humidity - Lee, Sangwon; Cho, Sujin; Jeong, Seok-Hyun; Lee, Wonkyu; Pyun, Dowon; Nam, Jiyeon; Hwang, Ji-Seong; Kim, Youngmin; Jang, Jihyun; Kang, Yoonmook; Kim, Donghwan; Lee, Hae-Seok (Communications materials, 2025)
CsPbI 3 , an inorganic perovskite with an excellent bandgap and thermal stability, exhibits great potential for Si-perovskite tandem solar cells although it is highly sensitive to moisture. Here we address this by fabricating CsPbI 3 solar cells under high humidity, controlling annealing via the humidity-dependent volatilization of dimethylammonium iodide. Surface passivation with 1,8-diaminooctane (DAO) reduces Pb surface defects, which enhances charge transport and forms a hydrophobic, moisture-resistant film. The DAO-passivated CsPbI 3 solar cell achieves a power conversion efficiency of 17.7% and retains 92.3% of its initial efficiency after 1500 minutes of maximum power point tracking in 30% relative humidity without encapsulation, demonstrating improved humidity stability. All solution-processed layers were fabricated in ambient air, highlighting their potential for cost-effective mass production. CsPbI₃ perovskite solar cells have potential for tandem applications but are sensitive to moisture. Here, CsPbI₃ cells under high humidity were fabricated using dimethylammonium iodide volatilization for precise annealing and 1,8-diaminooctane passivation to enhance efficiency and stability, achieving 17.7% efficiency.